2017
DOI: 10.1111/myc.12606
|View full text |Cite
|
Sign up to set email alerts
|

Inibitory effects of linalool on fungal pathogenicity of clinical isolates of Microsporum canis and Microsporum gypseum

Abstract: In humans worldwide, Microsporum sp. is a frequent agent of dermatophytsosis. When considering the emergence of resistant fungi and the clinical relevance of dermatophytosis, terpene antifungal activity is of great interest. Linalool is a monoterpene alcohol with pharmacological properties. In this study, antifungal in vitro activity of linalool and ketoconazole (as a positive control) were evaluated against clinical isolates of M. canis and M. gypseum. The minimum inhibitory concentration (MIC) and minimum fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Among all components of the sage volatile blends, the monoterpene alcohol linalool has been shown to have the strongest antifungal activity, while 1,8-cineole was only moderate, and linalyl acetate was lower [109][110][111]. The antifungal in vitro activity of linalool has been attributed to leakage of intracellular material that dramatically affects radial mycelial growth and conidial production and germination of treated pathogens with severity according to dose [112]. Ultrastructural studies carried out on Botrytis cinerea exposed to 1,8-cineole revealed detrimental effects on cell organelles [113].…”
Section: Sage Essential Oilsmentioning
confidence: 99%
“…Among all components of the sage volatile blends, the monoterpene alcohol linalool has been shown to have the strongest antifungal activity, while 1,8-cineole was only moderate, and linalyl acetate was lower [109][110][111]. The antifungal in vitro activity of linalool has been attributed to leakage of intracellular material that dramatically affects radial mycelial growth and conidial production and germination of treated pathogens with severity according to dose [112]. Ultrastructural studies carried out on Botrytis cinerea exposed to 1,8-cineole revealed detrimental effects on cell organelles [113].…”
Section: Sage Essential Oilsmentioning
confidence: 99%
“…The ways the microorganisms are inhibited by the essential oils seem to be distinguished by the mode of action and also to a variation in the penetration rate of the essential oil constituent through the cell wall and cell membrane structures [36]. According to Silva et al [37] essential oils act on bacterial cell membranes, impairing their structure and function, increasing their fluidity and permeability and, thus, inducing the leakage of intracellular materials, leading to cell damage and death. [38] state that the mechanism of action of essential oils and their constituents is not fully elucidated by the fact that in essential oils there are many phytochemical compounds and their antibacterial activity could not be attributed to a specific mechanism, but there are probably different targets in the bacterial cell.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The treatment of onychomycosis remains a relevant public health problem. Current drug treatments are effective, but resistant and biofilm-forming strains are emerging, causing therapeutic failures (Silva et al, 2017). Therefore, the need to search for new antifungal drugs against onychomycosis agents persists.…”
Section: Discussionmentioning
confidence: 99%